Factors associated with decision-making of replacing the temporary coronal restoration after endodontic treatment - Bárbara Scarton Fornari; Caroline Solda; Lara Dotto; Lilian Rigo (Universidade Estadual de Campinas, 2021)
Aim: This study aimed to evaluate the decision-making by patients to replace temporary restorations with permanent restorations after endodontic treatment and to verify the associated factors and evaluate the quality/integrity of the temporary restorative material within one month. Methods: This is a cross-sectional study using non-probabilistic sampling which analyzed patients after one month of endodontic treatment. The self-administered questionnaire contained sociodemographic, treatment decision-making and endodontic treatment questions. The restoration present in the mouth was evaluated in the clinical oral examination. The Poisson Regression test was used to verify the prevalence ratio. Results: The prevalence failure to perform permanent restorations was 61.1% of patients, and 42.7% reported not having adhered. The reasons are lack of time and not knowing the importance of replacing the restoration with a definitive one. The glass ionomer temporary restorative frequency was higher among those who chose not to replace the temporary restoration with a permanent one (PR=5.19; 95%CI 2.10-12.33). In addition, there was an association between the quality of the restorative material and the type of material, and the best clinical quality of the restoration was statistically associated with glass ionomer and composite resin. Conclusions: The findings show the importance of guidance by the dental surgeon in helping patients decide to replace their temporary restoration.